Upaya Meningkatkan Kemampuan Membaca Kata Melalui Metode Praktik Langsung dengan Kartu Huruf pada Anak Kelompok B TK Dharma Wanita II Mergowati Kecamatan Kedu Kabupaten Temanggung Semester II Tahun Pelajaran 2017/2018 - Suratiyah Suratiyah (Universitas PGRI Semarang, 2020)
Efforts to improve the ability to read words are an effort that gradually increases or enhances the ability or skills of children in translating spoken or written letters that have certain meanings. The rationale so that this problem arises is the low ability to read at the beginning of Group B TK Dharma Wanita II Mergowati. The objectives of this study are: 1) To find out that through the direct practice of the method with letter cards it can improve the ability to read words of children in Group B TK Dharma Wanita II Mergowati, Kedu District, Temanggung Regency, Semester II, 2017/2018 Academic Year, 2) To determine the magnitude of the increase in ability reading words through direct practice methods with letter cards in Group B children TK Dharma Wanita II Mergowati, Kedu District, Temanggung Regency, Semester II, 2017/2018 Academic Year.The subjects of this study were students of Group B TK Dharma Wanita II Mergowati totaling 20 children. The research was conducted from March to April 2018. The data collection methods used were observation, documentation, and interviews.Based on the results of research and discussion, it can be concluded that through direct practice with lettercard media can improve the ability to read words of children in Group B TK Dharma Wanita II Mergowati, Kedu District, Temanggung Regency, Semester II, 2017/2018 Academic Year. This is evidenced by an increase in children's pre-action reading skills before the action only reached 10%, then after the improvement in Cycle I increased to 45%, and Cycle II became 85%, having met the predetermined maximum percentage of 80%. This success is marked by the child being able to pronounce letter symbols that symbolize it, the child is able to compose letters into a meaningful word, the child is able to name groups of pictures that have the same initial/last sound/letter, the child is able to read and write simple words.